Perencanaan Enterprise Architecture pada Perusahaan Manufaktur PT. Z - Odwin Viator Hartedja; Leo Willyanto Santoso; Silvia Rostianingsih (Jurnal Infra, 2015)
PT.Z is a well-known producer and manufacturer of paint in Indonesia with years of experience in paint industry which produce many varieties of paint such as Decorative Coating (water and solvent based), automotive coating, Industrial Coating and Heavy Duty Coating. PT.Z has several subsidiaries all over Indonesia to elevate its product distribution. In the business process, PT.Z applies Information System to support and enhance the overall business. But, the current Information System applied is not subtle and disintegrated. Thus, it is a must for PT.Z to plan and create Enterprise Architecture with the method of Enterprise Architecture Planning. The process begins with doing analytical research of business model and Company’s business process. Afterwards, there will be analysis for Information Technology applied in PT.Z and the possible future problems regarding the Information Technology. The next step is to make the data architecture design, architecture application and architecture technology which comprehensive and suitable for the business purposes, strategies and business process. The result of Data Architecture Design, Application and the technology contains of eight sub information system, main application, supporting application and the use of Client/Server Architecture Pattern and Service Oriented Architecture.